Thoracic Imaging Findings of Collagen Vascular Diseases: A CT Study - Karam, Mehrdad Bakhshayesh (National Research Institute of Tuberculosis and Lung Disease, 2014)
BACKGROUND: Collagen vascular diseases (CVDs) are well known causes of pulmonary involvement, leading to significant morbidity. The purpose of this study was to identify several thoracic computed tomographic findings of CVDs. MATERIALS AND METHODS: The study included 56 patients (15 males and 41 females) with histopathologically and clinically proven CVDs who were identified retrospectively. The presence, extent and distribution of various CT findings were evaluated by a radiologist. RESULTS: Lung parenchyma (96.4%) was the most common area of involvement. The lower lobes (89.2%) were the most frequent sites of involvement. The predominant CT patterns were reticulation (55.3%), peripheral subpleural interlobular septal thickening (51.7%) and ground glass opacity (50%). The most common histopathological findings according to CT features were obliterative bronchiolitis (OB, 44.6%) and non-specific interstitial pneumonia (NSIP, 33.9%). Usual interstitial pneumonia was seen in 12.5% and organizing pneumonia in 26.7% of patients. CONCLUSION: A combination of reticular pattern, peripheral subpleural interlobular septal thickening and ground glass opacity is seen in the majority of patients with CVDs. The results indicate that OB is more prevalent than what has been reported in previous studies. The CT patterns of pulmonary fibrosis are similar to those in most other studies.